Cardiac insufficiency in elderly patients. A non-solve problem. - Angel Julio Romero Cabrera (Medisur)
Cardiac insufficiency is a clinical syndrome that is known since ancient times – more than 2000 years – in the pre Christian civilisation as Egypt, Greece and Old Rome where the digital plant was used as a remedy for this disease. As a syndrome it constitutes a point of convergence and many times the final stage of cardiac diseases but as it is known, cardiac insufficiency can be produced by non- cardiac disorders. This review is developed due to the necessity to update the guides about an unsolved problem of high frequency and a bad prognosis as well as to join the clinical practice with updated clinical evidence and to inform the most relevant aspects about cardiac insufficiency in the last few years.